Analysis Financial Distress of PT Sri Rejeki Isman Tbk: Altman Z-Score, Zmijewski, Zavgren Methods - Parihah, Nurul; Nur'aeni, Neni; Budianto, Erwin (Ilomata International Journal of Tax and Accounting, 2025)
Globalization that triggers increasingly sharp business competition requires the Company to act more strategically in order to avoid financial distress and bankruptcy. The textile and garment industry has an important role in the Indonesian economy, but faces financial distress due to decreased export demand and weak purchasing power, as experienced by Sritex in PKPU, so this study aims to analyze financial distress at PT Sri Rejeki Isman Tbk for the 2019-2023 period, using the Altman Z Score, Zmijewski and zavgren methods. The type of data in this study is secondary data obtained from the Company's published financial statements. The research method uses descriptive analysis with saturated sample technique in the form of financial statements of PT Sri Rejeki Isman Tbk listed on the Indonesia Stock Exchange (IDX). The results of this study indicate that the three approaches analyzed produce significant differences, especially based on the findings of the Altman Z Score method, which shows that PT Sri Rejeki Isman Tbk is likely to experience bankruptcy between 2021 and 2023. The Zmijewski method shows that in 2019 and 2020, experiencing financial difficulties but in the last three years the company has been in a healthy condition. The calculation results using the Zavgren method show that the company's condition in 2019 is classified as healthy, experiencing finacial distress in 2020 - 2021 and the company is back in a healthy condition in 2022-2023.